POLA PENGEMBANGAN WISATA ALAM DI KABUPATEN BOGOR - Farrah Muni (Jurnal Hospitality dan Pariwisata, 2017)
One area in Bogor regency has one of the most visitable place for tourist. It has tourismpotential and surely need to be well managed so that all the existed potentials can develop to be betterand more sustainable. The attraction that has highest offers potential among the six samples is KRBotani , while the lowest is KWA Gede Mountain. The shared problem of those attractions is the lack ofaccessibility to the attractions areas. The selected development strategies are improving the investmentclimate, performing maintenance of existing facilities, improving cleanness of areas, adding facilities,doing more massive promotion, repairing main road to the attractions, and improving coordinationbetween local government and attractions managers.Keywords: development, tourism, supply